Pemanfaatan Dana Desa Untuk Pengentasan Kemiskinan Melalui Metode Common Effect Model - Rini Armin; Nurdiana Fitri Isnaini; Eko Sutrisno (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
This study aims to determine the effect of capital adequacy ratio, loan to depositratio and non-performing loan on return on equity in banking companieslisted on the IndonesiaStock Exchange. This research is causal associative research and the type of data used isquantitative data. The data used is obtained from the company's financial statements that havebeen audited on the Indonesia Stock Exchange during the study period. The analytical methodused is descriptive analysis and multiple linear regression of panel data. The population of thisstudy is banking companies for the 2016-2020 period, which totals 40 companies. The sampleinthis study amounted to 36 companies. The results of this study indicate that the capitaladequacyratio has a positive and insignificant effect on return on equity, loan to deposit ratio has a positive and insignificant effect on return on equity, non-performing loans have a negative and significant effect on return on equity. Capital adequacy ratio, loan to deposit ratio and non- performing loan simultaneously have a significant effect on return on equity